Draft Five Year Plan 1978-83 Housing Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
In order to ameliorate the unsatisfactory housing condition in the country, the Government have been introducing a number of housing schemes since 1952. In view of limited financial resources however, the funds that are available for the purpose are, rather meagre in relation to the size of the problem. the problem of housing in the country as well as in the State is quite acute.
Government of Madhya Pradesh, Planning, Economics and Statistics Department